Aging and tumors: a dynamic interaction - Yudi Zhang; Siqiang Zhu; Zhaodong Liu; Yonghao Hu; Yongjian Zhang; Liang Shang; Leping Li (Discover Oncology)
Abstract Aging is an inevitable physiological process in organisms, and the development of tumors is closely associated with cellular senescence. This article initially examines the role of cellular senescence in tumorigenesis, emphasizing the correlation between telomere length—a marker of cellular senescence—and tumor risk. Concurrently, the study explores the expression levels of senescence-associated markers, such as p16, p53, and mTOR, in the context of tumor development. Additionally, the study investigates the impact of tumors on cellular and organismal senescence, including the effects on immune system function and metabolic processes. Ultimately, the discussion explores the potential application of anti-aging strategies in tumor therapy and considers the possibility of utilizing senescence mechanisms as a novel therapeutic approach for tumors. This research provides novel insights into the complex interplay between senescence and tumor development, suggesting potential strategies for future preventative measures and therapeutic interventions.